Strategy of sharia entrepreneurship education for nature-based High School students across Lampung Province - Farizi, Al (International Journal of Financial, Accounting, and Management, 2024)
Purpose: The purpose of this research is to explore the strategies and challenges in implementing sharia entrepreneurship education in nature-based senior high schools (SMA Alam) across Lampung Province, aiming to develop students who are both entrepreneurially skilled and grounded in Islamic economic values. Methodology: This study employed a qualitative approach, beginning with a literature review and needs analysis involving students, educators, and stakeholders. Data were collected through field observations and industry collaboration. The program's development followed a continuous cycle of monitoring and evaluation to refine implementation strategies based on feedback and outcomes. Results: The research found that the implementation of a holistic sharia entrepreneurship education strategy—covering curriculum development, industry involvement, active learning, extracurricular activities, and ongoing evaluation—effectively promotes entrepreneurial competence and Islamic character among students. Despite facing challenges such as limited understanding, resource constraints, and resistance to change, these can be addressed through targeted training, improved infrastructure, and stakeholder collaboration.